Intestinal barrier and dermatological diseases - V. A. Okhlopkov; E. A. Lyalyukova; E. N. Chernysheva; E. V. Nadey; A. V. Lyalukov (Лечащий Врач, 2021)
The purpose of the review is to analyze the literature data on the relationship between intestinal microbiocenosis disorders and skin diseases, as well as the effect of diet on the skin condition and features of the course of certain dermatological diseases. When analyzing the literature data, a close relationship between violations of intestinal microbiocenosis and the state of the intestinal barrier with skin diseases was confirmed. Western diet, low in fiber, vitamin D, high in fat, excess of gluten and simple carbohydrates, improving microbiome composition and intestinal permeability. In conditions of disturbed microbial balance and changes in the barrier functions of the intestine, the penetration of immunogenic molecules into the systemic circulation, including food antigens, bacterial toxins and pathogens, which can accumulate in the skin, disrupt the epidermal barrier, leading to chronic perception, increases. The task in the treatment of dermatological diseases is to eliminate increased intestinal permeability. There are several ways to restore the function of the intestinal barrier: 1) reducing or eliminating the intake of antigens, especially at a young age (for example, gluten-free diet); 2) changes in the composition of the microbiota (pre-, pros-, and antibiotics); 3) modification of proteins, intestinal barrier and other regulatory proteins (cytoprotectors); 4) elimination of inflammation leading to immune reactions.